2018
DOI: 10.3961/jpmph.18.090
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Prevalence of Childhood Asthma in Seoul Metropolitan City, Korea: The Seoul Atopy ∙ Asthma-friendly School Project

Abstract: ObjectivesThe project Seoul Atopy ∙ Asthma-friendly School investigated the current status of childhood asthma to enable formulation of a preventative policy. We evaluated the current prevalence of childhood asthma in Seoul and its trends and related factors.MethodsThe project was conducted annually from 2011 to 2016 and involved around 35 000 children aged 1-13 years. Based on the International Study of Asthma and Allergies in Childhood guidelines, the survey involved parents. The associations of the particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…First, since 2010, the Korean government and local governments have attempted to control childhood allergic diseases and have promoted research on exposure to outdoor and indoor environmental factors on allergic symptoms, and such efforts may have reduced the prevalence of asthma. 7) Moreover, asthma education is sufficiently provided over time by well-trained physicians. 18) Second, an influenza pandemic wave in 2009 to 2010 and a Mycoplasma pneumoniae pandemic wave in 2011 may be attributed to an increased risk of asthma, especially in vulnerable younger children and the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, since 2010, the Korean government and local governments have attempted to control childhood allergic diseases and have promoted research on exposure to outdoor and indoor environmental factors on allergic symptoms, and such efforts may have reduced the prevalence of asthma. 7) Moreover, asthma education is sufficiently provided over time by well-trained physicians. 18) Second, an influenza pandemic wave in 2009 to 2010 and a Mycoplasma pneumoniae pandemic wave in 2011 may be attributed to an increased risk of asthma, especially in vulnerable younger children and the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…1,2) However, the evidence supporting such trends in asthma, allergic rhinitis, and atopic dermatitis in Korea is controversial, as previous studies have reported both increasing [3][4][5][6] and decreasing prevalence. 2,[7][8][9] Furthermore, major questions remain regarding the age-stratified trends in allergic diseases and asthma in Korean populations. 10) To address these questions, we investigated the estimated agestratified prevalence and 10-year trends in 3 allergic diseases (asthma, allergic rhinitis, and atopic dermatitis), using data collected from the Korean National Health and Nutrition Examination Survey (KNHANES) from 2008 to 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Korean central and local governments' active policy against allergic diseases is one reason for the decrease in asthma. 7) For example, the Atopic Asthma Education Information Center and Atopy-Asthma-Friendly School Project aims to actively inform Koreans about disease prevention and management. 7) The most distinctive argument in the study by Ha et al 6) is that the withdrawal of humidifier disinfectants had a significant effect on reducing asthma rates.…”
mentioning
confidence: 99%
“…7) For example, the Atopic Asthma Education Information Center and Atopy-Asthma-Friendly School Project aims to actively inform Koreans about disease prevention and management. 7) The most distinctive argument in the study by Ha et al 6) is that the withdrawal of humidifier disinfectants had a significant effect on reducing asthma rates. In Korea, from 1994 to 2001, the extensive use of humidifier disinfectants was a serious risk factor that increased the prevalence of respiratory diseases including asthma and lung injury.…”
mentioning
confidence: 99%